Problemy stosowania controllingu oraz metody jego oceny - Nowosielski, Krzysztof (The problems of controlling exploitation and methods of its evaluation, 2006)
In the article controlling functioning problems in the enterprise were identified. In particular the attention was paid to these problems which concern low efficiency of controlling functioning and low quality of its services. The essence of controlling assessment was presented, as well as detailed literature analysis was conducted to find appropriate methods of such assessment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 119-126